Analysis of QoS for PAT and EnOPATr System in WSN - Avinash S, Devare; Krishna Mohan, G (International Journal of Engineering and Technology, 2018)
In the situations of natural disasters, Wireless Sensor Networks (WSN) is extensively used.  Quality of Service (QoS) is an important parameter for ensuring effectiveness and robustness of service provided.  QoS gets degraded when being applied in various applications of WSN.   Qos expected in WSN applications gets reduced further.  In this case, efficient use of the scarce resources is important to ensure continuous    data transmission is ensured by proficient use of resources which are limited resources. There are many WSN protocols which focus on broadcasting of important information. But there are many parameters which get neglected by these protocols. For instance, normal data traffic gets neglected by these protocols.  Hence, this research proposes EnOPATr system which is independent and distributed. The essential and normal data is handled at the same time in EnOPATr which achieves   dependable and congestion free data. In a sensor node, power consumption can be reduced by decreasing the rate of packet retransmission. This is because of congestion in network.  The simulation of the proposed system is done using NS-2 software which shows that the proposed system is able to reduce network congestion thereby improving the performance..